Multifocal Brown Tumors Imitating Giant Cell Tumor: A Case of Recurrent Bone Fractures and Preventable Amputation - Minahil Salam, Mudasira Ishtiaq, Sajjad Ahmed, Gohar Khan, Rimsha Azhar, Saira Bashir (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Brown tumor is a rare non-neoplastic focal lytic bone lesion occurring due to osteoclast overactivity secondary to hyperparathyroidism. Its incidence in patients with primary hyperparathyroidism is 1.5 to 1.7 %. These tumors mimic true bone neoplasms like giant cell tumors (GCT), posing significant diagnostic challenges. In addition, multiple brown tumors at diverse skeletal sites are significantly rare. Case presentation: We report the case of a 27-year-old male who presented with a fracture of the right forearm and left tibia after a minor fall. He had a history of recurrent long bone fractures and swellings along with marked weight loss, irritability, polyuria, polydipsia, bone pain, and deformities. Notably, he had undergone an above-knee amputation for a previously diagnosed giant cell tumor of the right lower limb. Physical examination showed hard, non-tender swellings over the left maxillary region and above the left knee joint. Imaging revealed multiple osteolytic lesions, while a neck ultrasound showcased a hypoechoic mass posterior to the left thyroid lobe. Laboratory findings indicated severe hypercalcemia, high levels of PTH, ALP, and hypophosphatemia. Definitive management included IV fluids and bisphosphonates, and later parathyroidectomy was performed, which revealed a parathyroid adenoma on biopsy. The patient is currently on follow-up and has normal calcium and PTH levels with no fractures reported. Discussion: This case highlights the importance of considering brown tumors in the differential diagnosis of multifocal osteolytic lesions. Literature review reveals a gap in clinical guidance on when to suspect BT in an apparent GCT, poorly understood differences in their molecular biology, and no standard criterion for distinguishing them on imaging. While hypercalcemia facilitates diagnosis, BT may rarely occur in pseudohypoparathyroidism, where elevated PTH coexists with normal serum calcium levels. Genetic testing, bone densitometry, and hormonal studies may potentially facilitate early detection, prevention, and informed family choices, yet are a challenge in resource-limited settings. Conclusion: Brown tumors should be ruled out in all cases of giant cell tumors for the avoidance of clinical misdiagnosis and improved patient outcomes. A simple routine biochemical test, including serum calcium and phosphate levels, can be the key to the prevention of harmful or unnecessary surgical interventions.